PENGGUNAAN VIDEO PEMBELAJARAN MUSEUM SANGIRAN PADA MATERI EVOLUSI HUBUNGANNYA DENGAN KETERAMPILAN PROSES SAINS DAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SMA - Bimantoro, Aldeila Meizatiesya; Handziko, Rio Christy (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
The objective of this study is to find out if using evolution learning videos is an appropriate solution to existing challenges, as well as to assess their impact on science process skills and critical thinking abilities in class XII at SMAN 2 Yogyakarta. This is a quasi-experimental study with a non-equivalent pre-test and post-test control group design. Purposive sampling is used in this study. The research classes were XII IPA 2 (control) and XII IPA 3 (experimental). The data collection strategies utilized include pretests and posttests, as well as non-test techniques such as learning implementation analysis sheets. Sampling was carried out three times: once before the test and twice after the test. The test is multiple-choice, with 15 questions based on markers of science process skills and critical thinking ability. The Mann-Whitney Test, Wilcoxon Test, Effect Size Test, and N-Gain Test can all be used to determine the effect of evolution learning films. The outcomes of this study indicate that evolution learning video media is an alternate solution for SMAN 2 Yogyakarta students that enhances their science process skills and critical thinking abilities.